Pemberian Pendidikan Kesehatan Melalui Telenursing terhadap Peningkatan Pengetahuan dan Pencegahan Keputihan Patologis pada Remaja - Yessi Andriani; Maidaliza Maidaliza; Rinona Iverta Alvaensi (Jurnal Kesmas Asclepius, 2020)
The purpose of this study was to determine the effect of providing health education through telenursing on increasing knowledge and prevention of pathological vaginal discharge in adolescents at SMK Negeri 2 Bukittinggi in 2020. This study used a quasy experimental method with a group pre-post test design. The results showed an increase in the mean level of knowledge and prevention of leucorrhoea, where the mean level of knowledge before and after health education was 12.77 and 27.18, while the mean prevention of vaginal discharge before and after health education was 18.55 and 33.82. The statistical test results obtained a p-value of 0.000 for the level of knowledge and a p-value of 0.000 for the prevention of pathological leucorrhoea. In conclusion, there is an effect of providing health education through telenursing on increasing knowledge and preventing pathological vaginal discharge. Keywords: Leucorrhoea, Health Education, Telenursing